Border Flows A Century of the Canadian-American Water Relationship - Macfarlane, Daniel; Heasley, Lynne (Canadian History and Environment, 2016)
Declining access to fresh water is one of the twenty-first century's most pressing environmental and human rights challenges, yet the struggle for water is not a new cause. The 8,800-kilometer border dividing Canada and the United States contains more than 20 percent of the world's total freshwater resources, and Border Flows traces the century-long effort by Canada and the United States to manage and care for their ecologically and economically shared rivers and lakes. Ranging across the continent, from the Great Lakes to the Northwest Passage to the Salish Sea, the histories in Border Flows offer critical insights into the historical struggle to care for these vital waters. From multiple perspectives, the book reveals alternative paradigms in water history, law, and policy at scales from the local to the transnational. Students, concerned citizens, and policymakers alike will benefit from the lessons to be found along this critical international border. With contributions by Andrea Charron, Alice Cohen, Dave Dempsey, Jerry Dennis, Colin A.M. Duncan, Matthew Evenden, James W. Feldman, Noah D. Hall, Lynne Heasley, Nancy Langston, Frédéric Lasserre, Daniel Macfarlane, Andrew Marcille, Jeremy Mouat, Emma S. Norman, Peter Starr, Joseph E. Taylor III, and Graeme Wynn